2020
DOI: 10.1002/bin.1758
|View full text |Cite
|
Sign up to set email alerts
|

A methodological review of preference displacement research

Abstract: The purpose of this review was to identify and compare methodological components of preference displacement research and outcomes. We coded, categorized, and defined patterns of preference displacement for a total of 133 participants across 10 studies. We found that patterns of displacement differed within and across studies, and over 46% of participants did not engage in patterns of displacement. Therefore, the commonly held notion that edible stimuli are more likely to displace tangible stimuli is not as ubi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Participants received 60 s access to preferred items during all preference and reinforcer assessments across the high‐tech and low‐tech conditions. Additionally, this study is the only study to date that used 60 s access to leisure items—prior research primarily provided 15–30 s access (White et al., 2021). Future research may extend these findings by examining displacement effects of high‐tech and low‐tech items while examining the effects of manipulating magnitude perhaps using procedures similar to Clark et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants received 60 s access to preferred items during all preference and reinforcer assessments across the high‐tech and low‐tech conditions. Additionally, this study is the only study to date that used 60 s access to leisure items—prior research primarily provided 15–30 s access (White et al., 2021). Future research may extend these findings by examining displacement effects of high‐tech and low‐tech items while examining the effects of manipulating magnitude perhaps using procedures similar to Clark et al.…”
Section: Discussionmentioning
confidence: 99%
“…White et al. (2021) conducted a methodological review of preference displacement research. Their review of 10 published studies identified that complete displacement of leisure items by edible items occurred in only 30% of participants across the reviewed studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent preference assessment studies have focused on preference displacement (e.g., Slanzi et al, 2020;White et al, 2021) and preference stability (e.g., Butler & Graff, 2021;MacNaul et al, 2021;Melanson et al, in press). For both preference displacement and preference stability, positional bias may influence their findings.…”
Section: A Need For Precise Measurement Of Positional Bias In Applied...mentioning
confidence: 99%
“…A research agenda on positional bias in MSWO assessments would not only allow researchers to understand how to systematically measure bias in an MSWO assessment but also to develop standardized bias levels. Recent preference assessment studies have focused on preference displacement (e.g., Slanzi et al., 2020; White et al., 2021) and preference stability (e.g., Butler & Graff, 2021; MacNaul et al., 2021; Melanson et al., in press). For both preference displacement and preference stability, positional bias may influence their findings.…”
Section: A Need For Precise Measurement Of Positional Bias In Applied...mentioning
confidence: 99%